SENSITIZATION PROGRAMME ON USAGE OF ORGANIC PADS DURING MENSTRUATION AMONG EARLY ADOLESCENT GIRLS AT VIJAYAPUR DISTRICT. - Agnihotri, Laxmi; Patil, Rupadevi; Kambi, Rajeshwari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The organic pads are made from 100% organic cotton and bamboo pulp. They are grown using natural processes without the use of any chemicals to ensure that it is safe to use. They are free from fragrances, and dyes which keep you free from rashes and are suitable for sensitive skin. Pre Experimental one group pre-test and post-test design was used. Based on the convinement sampling 100 adolescent girls were selected for this study. The girls who were attained menarche and aged between 17-20 years. In pre test 45% of adolescent girls were unaware of which chemical used in the pads, 80% adolescent girls don’t know about the garbage. In post test the 97% of adolescent girls know that organic pads are natural, 88 % girls are aware that, are made up of chemicals and 72% girls know that most of garbage produced by the disposable pads. the attitude of girls towards organic pads usage in pre test 70 % of girls not ready to prefer organic pads, 47 % girls thought that organic pads are costly,64% of girls told that organic pads inhibits the normal activities and 83% girls thought that organic pads are harmful to environment. In post test 81% girls preferred organic pads, 72% girls thought that organic pads are less cost, 94% girls are know that organic pads are not harmful to environment. Association between demographic variables with Attitude and knowledge were statistically not significant. Such as age, education, religion, menstrual history likes age at menarche, regularity and menstrual flow. The study concludes that, sensitization programme was effective in changing the knowledge and attitude of adolescent girls towards the usage of organic pads.